STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRODUKTIVITAS KINERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM HAGA LAKHOMI SAWANGAN DEPOK - Festina Gulo; Irma Sari Octaviani (Journal of Research and Publication Innovation, 2025)
This study aims to analyze human resource management (HRM) strategies in enhancing employee performance productivity at the Haga Lakhomi Savings and Loans Cooperative (Kophal) in Sawangan, Depok. In an era of intense business competition and rapid technological advancement, the quality and productivity of employees are key factors for organizational success, including cooperatives. The research employs a qualitative approach, utilizing data collection methods such as interviews, observations, and documentation. The findings indicate that the HRM strategies implemented include selective recruitment and employee selection, training and competency development, appropriate compensation, and improved internal communication. However, the study also identifies several challenges, such as limited quality of human resources, lack of technological proficiency, and suboptimal management. The conclusion emphasizes that the application of structured and sustainable HRM strategies significantly influences the improvement of employee work productivity and the operational effectiveness of the cooperative. This research is expected to serve as a reference for other cooperatives in strategically managing human resources.